FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MASYARAKAT JAKARTA DALAM MENGAKSES FORTAL MEDIA JAKARTA SMART CITY - Iin Soraya (Jurnal Komunikasi, 2015)
Jakarta Smart City is Fortal media established by the Government of DKI Jakarta, standing a year more and more people of Jakarta who access the site. Increased access of the media is interesting to do a study to analyze the factors that influenced the interest of the public to access media Fortal Jakarta Smart City. This type of research is quantitative descriptive, with a survey approach. Processing data using SPSS software version 20. The population is people who attend volunteer Activity numbered 120 people. The total sample of 30 people, with a sampling technique accidental sampling. Hypothesis testing using linaer multiple regression analysis, the coefficient of determination, Test f and t test intended to determine the effect of independent variables on the dependent variable. The results of this research are based Convergence Attention, Curiosity, Motivation, Needs, Family, Infrastructure and Environmental simultaneously affect the interest. Keywords: Jakarta Smart City, Interests, Fortal Media